Molecular dynamics simulation of model asphaltenes between surfaces of varying polarity. (1st January 2023) - Sun, Wenyuan; Zeng, Hongbo; Tang, Tian
Highlights: In water, C5Pe adsorbed on the alumina surface, instead of the siloxane surface. Enthalpy/entropy drove the adsorptions on the alumina/siloxane surfaces in water. Adsorption in toluene was enthalpy-driven and preferably on the alumina surface. In heptane, PMF calculations showed similar strength of binding to the two surfaces. Abstract: The molecular interaction behaviors of a model asphaltene, N-(1-Hexylheptyl)-N'-(5-carboxylicpentyl) perylene-3, 4, 9, 10-tetracarboxylic bisimide (C5Pe), between two solid surfaces of varying polarity, were studied by molecular dynamics simulations. The C5Pe molecules were solvated in water, toluene, or heptane, and the two substrate surfaces are hydrophilic alumina and relatively more hydrophobic siloxane surfaces (as model surfaces of two basal planes of kaolinite). Distinct adsorption behaviors were revealed by the simulations, which were driven and caused by the interaction of C5Pe molecules and surfaces of varying polarity in solvents of different nature. In water, both C5Pe monomer and aggregates adsorbed on the alumina surface, instead of the siloxane surface or staying in the liquid medium. Interestingly, in the control systems where a C5Pe molecule was placed between two identical surfaces in water, it displayed weaker adsorption when placed between two alumina surfaces than between two siloxane surfaces. Potential of mean force (PMF) calculations demonstrated the interplay between enthalpy-driven adsorption on the alumina surface and entropy-driven adsorption on the siloxane surface in water. In the adsorbed C5Pe aggregates on the alumina surface, the hydrophobic parts of the molecules stacked in a parallel manner and aligned perpendicularly to the alumina surface, while the hydrophilic parts formed hydrogen bonds with the surface. In toluene, C5Pe adsorbed on the alumina surface, driven by van der Waals and Coulomb interactions, as well as hydrogen bonding. A multi-layered C5Pe aggregate on the alumina surface in toluene was observed, which resulted from coordination bonds established through Ca 2+ between C5Pe molecules. In heptane, adsorption was found on both alumina and siloxane surfaces, and PMF calculations showed similar strength of binding to the two surfaces. The adsorbed aggregates were compact, with intermolecular π-π stackings that were parallel to the surfaces. This work provides a mechanistic understanding of the interaction behaviors of asphaltenes in solution media when different clay surfaces are simultaneously present, how such behaviors may be influenced by the nature of the solvent, and the molecular forces driving such behaviors.